Women's prelabour preference for epidural analgesia: a cross-sectional study among women from the Netherlands and Belgium. (March 2013) - Wassen, Martine; Miggiels, Lieke; Devlieger, Roland; Gyselaers, Wilfried; Mertens, Helen; Hasaart, Tom; Wijnen, Ella; Reu, Paul de; Roumen, Frans; Nijhuis, Jan; Smits, Luc; Scheepers, Hubertina
Abstract: Background : This study describes variables related to women's prelabour preference for epidural analgesia (PEA) in two neighbouring countries with a comparable socio-economic and cultural background. Methods : Dutch women in midwifery ( n  = 164) or obstetrical care ( n  = 162), and Belgian women ( n  = 188) of ≥36 weeks gestation with a singleton in cephalic presentation completed questionnaires on demographic factors, received labour analgesia information, perceived attitude of the caregiver towards epidural analgesia (EA), pain catastrophising and coping with labour pain. Multiple logistic regression analysis was performed with PEA as dependent variable. Results : PEA was 9.9% in Dutch midwifery care, 25.5% in Dutch obstetrical care and 38.3% in Belgian care ( p value < 0.001). In the Netherlands, maternal age of 35 years or older (OR 4.95; 95% confidence interval (CI) 2.03–12.08), positive attitude of the caregiver towards EA (OR 5.83; 95% CI 2.57–13.23) and a lower degree of coping (OR 3.61; 95% CI 2.24–5.82) were independently associated with PEA. In Belgium, only a lower degree of coping was associated with PEA (OR 4.06; 95% CI 2.45–6.73). Conclusions : In both countries, women with a lower degree of coping had a higher PEA. Care setting in the Netherlands was not an independent variable.